Elevated Expression of Notch1 Is Associated With Metastasis of Human Malignancies. (October 2013) - Zhu, He; Zhou, Xinchun; Redfield, Samantha; He, Zhi; Lewin, Jack; Miele, Lucio
The expression level of Notch1 has been studied in many primary tumor types, but has not been widely investigated in metastatic lesions from human malignancies. Using immunohistochemistry (IHC), the expression level of Notch1 was evaluated and compared between primary and metastatic tumors in 12 different cancers. The mean IHC score of Notch1 was significantly increased in metastatic hepatocellular carcinoma (HCC; 5.4 ± 0.7) and in metastatic renal cell carcinoma (RCC; 5.0 ± 2.3) compared with primary HCC (3.1 ± 0.7, P = .035) and RCC (1.3 ± 0.6, P = .049), respectively. Similarly, the expression level of Notch1 showed an increasing trend in the metastatic malignancies in the larynx, prostate, and stomach compared with corresponding primary malignancies ( P values are .055, .072, and .074, respectively). The results demonstrate elevated expression of Notch1 in some metastatic tumors, suggesting that Notch1 may play an important role in the development or maintenance of metastatic lesions, and targeting of Notch1 might be a therapeutic approach against tumor metastasis.